Implementation of Blockchain Technology: Analysis of Sharia Banking Financial Transactions in Indonesia - Ade Rani Octaviana (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines the application of Blockchain technology in Sharia Banking in Indonesia through a combination of analytical and descriptive approaches. A comprehensive literature review was conducted to understand the application of Blockchain technology in the financial industry, especially Sharia Banking. This research identifies important variables such as transparency, transaction security, operational efficiency, customer trust, and sharia compliance. The results of this study show that the application of Blockchain technology can improve the operational efficiency of Sharia Banking, transparency and transaction security. In addition, Blockchain helps in complying with sharia rules by reducing the risk of manipulation and usury. Nonetheless, challenges such as standardization, infrastructure, and client education need to be addressed to maximize the benefits of Blockchain in Sharia Banking. These findings highlight the importance of the application of Blockchain technology in improving security, efficiency, and transparency in Sharia Banking operations.